Effect of Picolinic Acid and Dipicolinic Acid on the Stability of Mixed Ligand Cu (II) Complexes Containing Amino Acids - Mohan, Allam; Radha, K.; Srinivas Mohan, M. (Asian Journal of Chemistry, 2010)
Formation constants of mixed ligand Cu(II) complexes [MLA] whereL = picolinic acid (PA) or dipicolinic acid (DPA) and A = alanine, serinethreonine, methionine, phenylalanine, tyrosine and tryptophan were determinedby potentiometric pH titrations at 35ºC and μ= 0.2 (KNO3) andthe stability of the mixed ligand and the corresponding binary complexeswere quantitatively compared in terms of the parameter Δ log K(Δ log K = log KMLMLA – log KMMA). Mixed ligand complexes containing PAas primary ligand were found to be more stable than the correspondingcomplexes containing DPA. In mixed complexes involving PA, the aminoacids with an aromatic side chain, viz., phenylalanine, tyrosine and tryptophanexhibit enhanced stability due to intramolecular metal ion mediatedstacking interactions between the aromatic moieties of the two ligands,and the intramolecular equilibrium between the stacked and open forms,have been evaluated. Due to sterle considerations stacking interactionswere not observed in DPA containing mixed complexes.